Halting hyaluronidase activity with hyaluronan-based nanohydrogels: development of versatile injectable formulations. (1st October 2019) - Montanari, E.; Zoratto, N.; Mosca, L.; Cervoni, L.; Lallana, E.; Angelini, R.; Matassa, R.; Coviello, T.; Di Meo, C.; Matricardi, P.
Highlights: Hyaluronan-cholesterol nanohydrogels inhibit hyaluronidase activity, halting the enzymatic degradation of hyaluronan. Hyaluronan-cholesterol nanohydrogels bind to hyaluronidase with an affinity constant higher than that of hyaluronan. Development and characterisation of versatile hyaluronidase-resistant injectable mixtures for viscosupplementation and dermo-cosmetic applications. Abstract: Hyaluronan (HA) is among the most used biopolymers for viscosupplementation and dermocosmetics. However, the current injectable HA-based formulations present relevant limitations: I) unmodified HA is quickly degraded by endogenous hyaluronidases (HAase), resulting in short lasting properties; II) cross-linked HA, although shows enhanced stability against HAase, often contains toxic chemical cross-linkers. As such, herein, we present biocompatible self-assembled hyaluronan-cholesterol nanohydrogels (HA-CH NHs) able to bind to HAase and inhibit the enzyme activity in vitro, more efficiently than currently marketed HA-based cross-linked formulations ( e.g. Jonexa™). HA-CH NHs inhibit HAase through a mixed mechanism, by which NHs bind to HAase with an affinity constant 7-fold higher than that of native HA. Similar NHs, based on gellan-CH, evidenced no binding to HAase, neither inhibition of the enzyme activity, suggesting this effect might be due to the specific binding of HA-CH to the active site of the enzyme. Therefore, HA-CH NHs were engineered into injectable hybrid HA mixtures or physical hydrogels, able to halt the enzymatic degradation of HA.